LIFE CYCLE AND BEHAVIOR OF Salpingogaster nigra SCHINER, PREDATOR OF "MION" AND "SALIVITA" OF PASTURES - PÁEZ, PEDRO JOSÉ; TORRES-M., GERMÁN ALONSO; JIMÉNEZ-G., JAIME A.; LUQUE-Z., JESÚS E. (Revista Colombiana de Entomología, 1985)
The life cycle of Salpingogaster nigra Schiner, a natural enemy of the froghoppers Aeneolamia varia (F.) y Zulia pubescens (F.), was studied under field and laboratory conditioris at the farm "San José" in Medina (Cund.) and at the Centro Regional de In\Jstigaciones "La Libertad" in Villavicencio. The life cycle lasted in total 27.37 days, divided in: egg 2.7 days, calculated for the larva 9.7 days, pupa 9.67 days, and an average of 5.3 days for the adult. Based on morphometric studies it was determined that the larva has three instars. The larva consumes between 14 and 20 nymphs of the pest. The description of the stages and some behavioral observations are presented.